Association of Systemic Diseases with Chronic Pruritus: CHRONIC PRURITUS - Jovičić, Sanja; Balaban, Jagoda; Gajanin, Vesna (Scripta Medica, 2023)
Background/Aim: Pruritus is an unpleasant sensation that provokes the desire to scratch. It is one of the most common reasons why patients consult a dermatologist. Aim of this study was to determine the association of chronic pruritus with skin and systemic diseases, as well as the age and sex distribution in the studied population.Methods: The cross-sectional study included 120 patients of both sexes who, in the period from January 2017 to January 2021, received outpatient and inpatient treatment at the Skin and Venereal Diseases Clinic of the University Clinical Centre of the Republic of Srpska diagnosed with pruritus. Through the Clinical Information System insight was gained into the medical history and other documentation of the subjects from which data were taken on the age and sex of the subjects, onset, course and duration of pruritus, daily or seasonal variations in intensity, as well as the presence of associated skin and systemic diseases.Results: Out of a total of 120 subjects, a larger number (53.3 %) of subjects with chronic pruritus were male, and 46.7 % were female, the difference was statistically significant (p < 0.05). The analysis of the distribution of subjects according to their age revealed that the largest number of subjects (62.6 %) was over 65 years of age, while 38.4 % of subjects were under 65 years of age. The difference in the age structure was statistically significant (p < 0.05). In subjects older than 65 years pruritus was most frequently (47.3 %) associated with diabetes and in subjects under 65 years of age with skin diseases and conditions. The difference was statistically significant (p < 0.05).Conclusion: In people aged over 65 years, pruritus is most frequently associated with systemic diseases (diabetes mellitus) and in people aged under 65 years with dermatological diseases (Dermatitis atopica).
Keywords: Chronic pruritus; Diabetes mellitus; Senile pruritus